Tattooed Bodies
XVIII, 358 p. 23 illus., 22 illus. in color.
Keywords: “Tattooed Bodies—apart from often being an exemplary model of Continental philosophy—is a groundbreaking contribution to tattoo studies that shows us how tattooing, when taken seriously, can open up the meanings of works of art, literature, film, and theory itself in unexpected ways. For those who have already been thinking about the meaning of “the tattoo,” this collection of essays will greatly expand possibilities of inquiry. For those who are new to the field, several essays act simply as excellent primers on how to undertake deconstructive, anthropological, aesthetic analysis in general offering up scholarly, nuanced investigations of texts without indulging in exclusionary jargon.” -Danielle Meijer, DePaul University "What is a tattoo? Associated in the past with criminals and degenerates, tattoos have become high fashion in the 21st century. In this collection, leading scholars speculate about the nature and implications ofthese bodily inscriptions. Are they social or antisocial? Conformist or rebellious? Decorative or disfiguring? Atavistic or futuristic? How do they relate to other scars, such as the navel as the mark of our maternal origin? By opening up these questions and many more, the essays in this volume show how the tattoo challenges the distinction between word and flesh, self and society, life and death.” -Maud Ellmann, University of Chicago The essays collected in Tattooed Bodies draw on a range of theoretical paradigms and empirical knowledge to investigate tattoos, tattooing, and our complex relations with marks on skin. Engaging with perspectives in art history, continental philosophy, media studies, psychoanalysis, critical theory, literary studies, biopolitics, and cultural anthropology, the volume reflects the diversity of meanings attributed to tattoos across cultures. Essays explore tattoos and tattooing in Derrida, Deleuze and Guattari, Lacan, Agamben, and Jean-Luc Nancy, while interpreting tattoos in literary works by Melville, Beckett, Kafka, Genet, and Jeff VanderMeer, among others. James Martell is Associate Professor of French at Lyon College, USA. Erik Larsen is Assistant Professor of Medical Humanities at the University of Rochester, USA.